Estimulación sensorial y su impacto en el desarrollo socioemocional en niños de Educación Inicial I - Burgos Macías, Ashly Gissel (2025)
Sensory stimulation plays a crucial role in socio-emotional development during early childhood, a fundamental stage for laying the foundations for learning and interpersonal relationships. This study aims to determine the impact of sensory stimulation on the socio-emotional development of children in Early Childhood Education I at the Juan E. Verdesoto Basic Education School, in the city of Babahoyo, province of Los Ríos, during the 2024-2025 school year, since it was identified that children have difficulties in emotional expression, impulse control and social interactions, aspects that limit their well-being and integral development. Although teachers are aware of the relevance of socio-emotional development, current pedagogical strategies do not adequately address this aspect. The methodology used was a qualitative approach, with a non-experimental, analytical-synthetic design. Data were collected through interviews with teachers, observations of children and surveys of parents. Among the results obtained from the applied instruments, it was detailed that there is a lack of socio-emotional skills in children, which is why it is necessary to promote communication and teamwork through new strategies. It was concluded that sensory stimulation directly impacts curiosity, social interaction and emotional self-regulation since children, through the manipulation of materials, explore their environment, experience new sensations and develop skills to express themselves and manage their emotions.